Pattern of critical literacy learning planning in boarding schools based - Dewi Tryanasari; Anang Santoso; Djoko Saryono; Titik Harsiati (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2024)
Planning learning is stages important in learning. Planning good learning is one guaranteed aspect quality learning. Literacy critical teach importance see A text as representation of the world that is not neutral. this article discuss about pattern planning learning literacy critical especially in writing critical at school medium the first to take shelter below foundation owned by boarding school Islamic boarding schools are very thick with Islamic religious rules and observance against clerics as leader whereas literacy critical teach freedom For think and question text as something that is tendentious. With thereby topic literacy critical at school based boarding school is unique phenomenon. this article based approach _ study qualitative phenomenology with object and subject study learning research conducted by teachers in grade 8. From the results study can concluded that planning learning literacy critical at school based boarding school adhere backward design pattern where results end learning determined especially formerly Then new done analysis need as well as step learning For reach objective end. Learning literacy critical at school based boarding school teach students to think critically and objectively by taking into account social, cultural and character values that are not contrary to the Islamic religion.